Impact of Nutrient Availability on the Fermentation and Production of Aroma Compounds Under Sequential Inoculation With M. pulcherrima and S. cerevisiae - Seguinot, Pauline; Ortiz-Julien, Anne; Camarasa, Carole (Frontiers in Microbiology, 2020)
Non-Saccharomyces yeasts are currently widely used in winemaking to enhance aroma profile diversity among wines. The use of M. pulcherrima in sequential inoculations with S. cerevisiae was compared to the inoculation of a pure cultures of S. cerevisiae. Moreover, various concentrations of sugar, nitrogen and lipids were tested in synthetic must to assess their impact on fermentation and its outcomes using a Box-Behnken design. Due to its phenotypic specificities, early inoculation with M. pulcherrima led to important modifications, first altering the fermentation kinetics. This may relate, at least in part, to the depletion of some nitrogen sources by M. pulcherrima during the first part of fermentation. Beyond these negative interactions on fermentation performance, comparisons between pure cultures and sequentially inoculated cultures revealed changes in the distribution of carbon fluxes during fermentation in presence of M. pulcherrima, resulting in a positive impact on the production of central carbon metabolites and aromas. In particular, the expression of varietal thiols was strongly increased as a consequence of positive interactions between the two species. The mechanism of this release still needs to be investigated. Significant differences in the final concentrations of fermentative and varietal aromas depending on the initial must composition were obtained under both inoculation strategies. Interestingly, the response to changes in nutrient availability varied according to the inoculation modality. In particular, a greater incidence of lipids on the production of fatty acids and their ethyl esters derivatives was found during sequential fermentation compared with pure culture, to be viewed in combination with the metabolic characteristics of M. pulcherrima regarding the production of volatile compounds from acetyl-CoA. Overall, the importance of managing nutrient availability under M. pulcherrima / S. cerevisiae sequential inoculation in order to derive the maximum benefit from the potentialities of the non-Saccharomyces species while carrying out fermentation to dryness was highlighted.